2018
DOI: 10.3390/nu10030268
|View full text |Cite
|
Sign up to set email alerts
|

MS Sunshine Study: Sun Exposure But Not Vitamin D Is Associated with Multiple Sclerosis Risk in Blacks and Hispanics

Abstract: Multiple sclerosis (MS) incidence and serum 25-hydroxyvitamin D (25OHD) levels vary by race/ethnicity. We examined the consistency of beneficial effects of 25OHD and/or sun exposure for MS risk across multiple racial/ethnic groups. We recruited incident MS cases and controls (blacks 116 cases/131 controls; Hispanics 183/197; whites 247/267) from the membership of Kaiser Permanente Southern California into the MS Sunshine Study to simultaneously examine sun exposure and 25OHD, accounting for genetic ancestry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Observational studies similarly show that lower 25OHD levels are associated with increased MS risk in White populations . A similar association is not seen in Hispanics and Blacks . Within White populations, the dose–response relationship is inconsistent; for example, both threshold (e.g.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 98%
See 1 more Smart Citation
“…Observational studies similarly show that lower 25OHD levels are associated with increased MS risk in White populations . A similar association is not seen in Hispanics and Blacks . Within White populations, the dose–response relationship is inconsistent; for example, both threshold (e.g.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 98%
“…These inconsistent associations may be because few studies have accounted for sun exposure. Where data are available on both sun exposure and 25OHD levels, there are statistically independent benefits of higher levels of either in Whites . Both UV radiation and vitamin D have effects on innate and adaptive immune function that would plausibly be beneficial for MS …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…Sun exposure is the principal source of vitamin D and evidence indicates a protective role for higher vitamin D levels [19,20]. However, a multi-ethnic study observed that sun exposure reduced the risk of MS regardless of race/ethnicity, whereas vitamin D deficiency was only associated with MS risk among whites [21]. Several studies have reported that sun exposure and vitamin D are independently associated with decreased MS risk [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of consistency for 25(OH)D levels across races seems biologically implausible, but may be explained by the weaker correlation between recent sun exposure and 25(OH)D levels in darker skinned, compared to lighter skinned, individuals [33], i.e., 25(OH)D reflects recent sun exposure, rather than vitamin D per se. Nevertheless, a nested case-control study within a large cohort study showed that higher total vitamin D intake (from diet and supplements, when supplements were assumed to contain 400 IU of vitamin D) was associated with reduced risk of MS [44].…”
Section: Sun Exposure or Vitamin D?mentioning
confidence: 99%